All Days 1999
DOI: 10.2118/54763-ms
|View full text |Cite
|
Sign up to set email alerts
|

Return Permeability: A Detailed Comparative Study

Abstract: This paper was prepared for presentation at the 1999 SPE European Formation Damage Conference held in The Hague, The Netherlands, 31 May–1 June 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…There is no standard manufacturer for this type of testing apparatus (Marshall et al 1999) so it is highly unlikely that any two laboratories employ the same exact equipment. It is interesting to note the development of the return permeability method and associated equipment as early publications document.…”
Section: Basic Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is no standard manufacturer for this type of testing apparatus (Marshall et al 1999) so it is highly unlikely that any two laboratories employ the same exact equipment. It is interesting to note the development of the return permeability method and associated equipment as early publications document.…”
Section: Basic Methodsmentioning
confidence: 99%
“…However, Marshall et al (1997 concludes that return permeability measurement is one of the most common evaluation tools used for selecting an RDF system. Attempts to standardize, establish repeatability or reproducibility, and improve return permeability testing are also well documented (Marshall et al 1997;Marshall et al 1999;Byrne et al 2011). Han et al (2005) presents a means to bridge the gap between the laboratory-measured data and field skin factors while focusing on laboratory-measured fluid loss.…”
Section: Basic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…But generally these studies were conducted on small pieces of core samples (2 to 5 cm), on metallic porous disks or sometimes on filter papers initially saturated with brine only and under operating conditions quite far from those prevailing in wells (pressure, temperature, shear rate, etc.). More recently a comparative study was performed in order to establish a standardized methodology for formation damage testing 8 . The results, obtained on short cores on which a large dispersion of fluid losses (spurt and filtration rates) was observed, showed that a good level of repeatability and/or reproducibility has not been achieved.…”
Section: Development Of Enhanced Laboratory Testing Proceduresmentioning
confidence: 99%